RITUAL SPEECH OF LUKAH GILO TRADITION OF BONAI SOCIETY: VALUE AND SOCIAL FUNGTION TEXT STUDY - Misra Nofrita (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
This article contains information on the tradition of the lukah gilo community of Bonai, Rokan Regency upstream which is reviewed in terms of the values and social functions of the text. There is also a method used is descriptive method. Descriptive method is a method used to examine an object, a thought or an event in the present. The results showed that speech in the tradition of lukah gilo based on social values and functions oftext the Lukah Gilo traditionalhad several functions including (1) as a means of entertainment; (2) As a tool to maintain and pass on customs, traditions and culture; (3) group identity and (4) cultural validation.